1996
DOI: 10.1039/cc9960002549
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterisation of C60F18

Abstract: C60F18 has been prepared by reaction between [60]fullerene and potassium hexafluoroplatinate in a Knudsen cell contained within a mass spectrometer; characterisation by l9F NMR spectroscopy shows that the molecule has C3" symmetry and is isostructural with C60H18.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
137
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 139 publications
(146 citation statements)
references
References 4 publications
8
137
1
Order By: Relevance
“…Preparation of C 60 F 18 : A small-scale preparation of C 60 F 18 has been described before [22] but was prepared for this work in two ways:…”
Section: Methodsmentioning
confidence: 99%
“…Preparation of C 60 F 18 : A small-scale preparation of C 60 F 18 has been described before [22] but was prepared for this work in two ways:…”
Section: Methodsmentioning
confidence: 99%
“…Thus, a crownshaped structure of C 60 F 18 points to the C 3v symmetry [11], the consideration of T, C 3 , S 6 , and D 3d structures for C 60 F 36 has allowed for decreasing the isomer number to 63 [14], 94 isomers have been selected in the case of C 60 F 48 [13]. The justification of the assumption has been mainly based on the 19 F NMR spectra of C 60 F 18 [18], C 60 F 36 [19], and C 60 F 48 [20,21]. However, a thorough analysis of both 19 F NMR and 2d COSY spectra has shown that the structure assignment, based on the theoretical predictions, is not absolutely secure, particularly for C 60 F 36 and C 60 F 48 species (a detailed discussion see in Section 5.4).…”
Section: Introductionmentioning
confidence: 99%
“…[26] The much longer retention time of C 60 F 18 is consistent with its greater polarity. [27] The C s symmetry of C 60 F 16 , [24] the precursor to C 60 F 18 , [26] is lower than the C 3v symmetry of C 60 F 18 , which would account for the still higher polarity of C 60 F 16 .…”
Section: Resultsmentioning
confidence: 98%